Association of obesity and risk of diabetic retinopathy in diabetes patients: A meta-analysis of prospective cohort studies - Zhu, Wei (Medicine (Baltimore), 2018)
BACKGROUND: Diabetic retinopathy (DR) was considered to be a common complication of diabetes. The purpose of the current study was to investigate the potential association between obesity and DR risk by conducting a meta-analysis of prospective studies. METHODS: A consummate literature search of PubMed, EMBASE, and web of science was conducted until July 2016. A total of 13 prospective cohort studies were included in this meta-analysis. RESULTS: On meta-analysis of all the studies assessing DR risk, obesity was associated with a significant increase in DR incidence (relative risk [RR], 1.20; 95% confidence interval [CI], 1.01–1.43; I(2) = 59.6%). When only proliferative DR (PDR) was considered, no significant association between obesity and risk of PDR was detected. Significant harmful effect was detected in type 2 diabetes mellitus (T2DM) group (RR, 1.40; 95% CI, 1.05–1.87; I(2) = 67.6%) but not mixed group (RR, 1.04; 95% CI, 0.97–1.18; I(2) = 0.00%). No significant publication bias was detected in the selected 13 studies. CONCLUSION: Obesity was a risk factor for non-proliferative DR. However additional well-designed and well-conducted epidemiologic studies were required to deepen our understanding of the relation between obesity and DR.